If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -2) = 3 + 3x Reorder the terms: 7(-2 + x) = 3 + 3x (-2 * 7 + x * 7) = 3 + 3x (-14 + 7x) = 3 + 3x Solving -14 + 7x = 3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -14 + 7x + -3x = 3 + 3x + -3x Combine like terms: 7x + -3x = 4x -14 + 4x = 3 + 3x + -3x Combine like terms: 3x + -3x = 0 -14 + 4x = 3 + 0 -14 + 4x = 3 Add '14' to each side of the equation. -14 + 14 + 4x = 3 + 14 Combine like terms: -14 + 14 = 0 0 + 4x = 3 + 14 4x = 3 + 14 Combine like terms: 3 + 14 = 17 4x = 17 Divide each side by '4'. x = 4.25 Simplifying x = 4.25
| 19=x-7 | | 14=3/2x-7 | | x/456=4 | | x/4456=4 | | 2x-14=2(2x+3) | | 9x-7=23x-14 | | x-2.6=7.3 | | 27=46+2x-1x | | 1.5m=0.5 | | -6x-21+9x=42 | | 2x+6=-7x-9 | | 27-(x+9)=4x-2 | | 6x-(2x+4)-(x+3)= | | 7(2y+1)=2(y-13) | | 0.4=0.75+y | | -6b+5(1-b)=-8b+26 | | (2x-1)(x^2-3x+5)=0 | | 3(2x+1)+1+2x=3(2x+2)+x | | 2X^2-16X+64= | | 7y-9-4y+4=0 | | 1.2x=40.8 | | 0(2x-4)^-11/2 | | -5+x-9=15 | | -1/4a7/4a=-21 | | 3/5x-3=2.25 | | 0.4=0.75y | | -(-5-6n)-3(2n+3)=3 | | 3x+4=-2x-14 | | -12-1x=8-3x | | 5x-3y=10fory | | -6=m+(-25) | | 3x/4=2 |